He and Ne in individual chromite grains from the regolith breccia Ghubara (L5): Exploring the history of the L chondrite parent body regolith. (28th February 2014) - Meier, Matthias M. M.; Schmitz, Birger; Alwmark, Carl; Trappitsch, Reto; Maden, Colin; Wieler, Rainer
Abstract: We analyzed He and Ne in chromite grains from the regolith breccia Ghubara (L5), to compare it with He and Ne in sediment‐dispersed extraterrestrial chromite (SEC) grains from mid‐Ordovician sediments. These SEC grains arrived on Earth as micrometeorites in the aftermath of the L chondrite parent body (LCPB) breakup event, 470 Ma ago. A significant fraction of them show prolonged exposure to galactic cosmic rays for up to several 10 Ma. The majority of the cosmogenic noble gases in these grains were probably acquired in the regolith of the LCPB (Meier et al. 2010 ). Ghubara, an L chondritic regolith breccia with an Ar‐Ar shock age of 470 Ma, is a sample of that regolith. We find cosmic‐ray exposure ages of up to several 10 Ma in some Ghubara chromite grains, confirming for the first time that individual chromite grains with such high exposure ages indeed existed in the LCPB regolith, and that the >10 Ma cosmic‐ray exposure ages found in recent micrometeorites are thus not necessarily indicative of an origin in the Kuiper Belt. Some Ghubara chromite grains show much lower concentrations of cosmogenic He and Ne, indicating that the 4π (last‐stage) exposure age of the Ghubara meteoroid lasted only 4–6 Ma. This exposure age is considerably shorter than the 15–20 Ma suggested before from bulk analyses, indicating that bulk samples have seen regolith pre‐exposure as well. The shorter last‐stage exposure age probably links Ghubara to a small peak of 40 Ar‐poor L5 chondrites of the same exposure age. Furthermore, and quite unexpectedly, we find a Ne component similar to presolar Ne‐HL in the chromite grains, perhaps indicating that some presolar Ne can be preserved even in meteorites of petrologic type 5.